A patient-centredness improvement study for efficacy of behaviour change for healthy lifestyle and weight loss in a student-run free clinic. (15th July 2020) - Lessans, Spencer; Vega, Xamil; Foley, Brandon; Bossan, Alexia; Baker, Alexandra; McElroy, Mitchell; Crouse, Eloisa; Pasarica, Magdalena
Abstract: Background: Primary care is the ideal place to implement behaviour change interventions for weight management. However, most primary care physicians are not managing patient weight as a standard of care due to lack of knowledge, skills and reimbursement. Generating more physicians who are familiar and comfortable with providing weight management is essential in leveraging a global change. In our university free clinic, medical students provide healthy lifestyle counselling using shared decision making to each patient at every clinic visit. Objective: Improve the efficacy of behaviour change interventions via increased patient responsiveness and adherence. Methods: The needs assessment demonstrated a subpar patient response rate to check-ins regarding behavioural change goals. In the first and second interventions, check-in message structure and contact schedule were varied to maximize patient responsiveness and goal achievement. Results: In the needs assessment, 58% of patients responded to follow-ups and 58% of patients accomplished their goal. The first intervention cycle resulted in an improvement of responsiveness to 70% and accomplishment of goals to 59%. The second intervention cycle resulted in an improvement of responsiveness to 78% and accomplishment of goals to 74%. Conclusions: Messages that were frequent, unique, succinct and delivered within 4 weeks after the clinic visit resulted in the highest response rate and goal attainment. Other primary care clinics can use these interventions to increase patient completion of implemented behaviour changes for a healthier lifestyle.